2019
DOI: 10.1111/cod.13343
|View full text |Cite
|
Sign up to set email alerts
|

Delayed hypersensitivity to palladium dichloride: 15‐year retrospective study in a skin allergy unit

Abstract: Background Metal allergies are the most frequent causes of allergic contact dermatitis. Although the use of palladium is increasing, it is not included in any baseline series. Objective To assess the prevalence of hypersensitivity to palladium and to describe the clinical and demographic characteristics of patients who are sensitized to palladium dichloride (PdCl2). Methods A single‐centre, retrospective study of 15 years of patch testing with the Spanish baseline series supplemented with PdCl2 2% pet. was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
4
11
1
1
Order By: Relevance
“…In consecutively (routinely) patch-tested Spanish patients (n = 3678), palladium dichloride 2% pet. caused 8.6% positive reactions; only 26/316 positive patients were not also sensitised to nickel [46], confirming observations made elsewhere [47]. Patch test reactions to vanadium (tested as trichloride 1% pet.)…”
Section: Metalssupporting
confidence: 86%
“…In consecutively (routinely) patch-tested Spanish patients (n = 3678), palladium dichloride 2% pet. caused 8.6% positive reactions; only 26/316 positive patients were not also sensitised to nickel [46], confirming observations made elsewhere [47]. Patch test reactions to vanadium (tested as trichloride 1% pet.)…”
Section: Metalssupporting
confidence: 86%
“…Depending on the study, between 2.3 and 72% of Ni-allergic patients also react to Co 2+ with a positive patch test reaction [82,242,243]. Between 11 and 40% of Ni-reactive individuals respond to Pd 2+ [87,242,243]. In several studies, up to 83% co-sensitization of Co-allergic patients to Ni 2+ is also observed in combination with other metals [244,245].…”
Section: Tcr Cross-reactivity To Ni Co and Pdmentioning
confidence: 98%
“…Additionally, Pd is present in jewelry and industrial catalysts in the car industry because of its resistance to corrosion [2]. Although the use of Pd is increasing, it is not included in any standard test baseline series [87]. Out of 910 ACD patients in the USA, 12.1% tested positive for Pd.…”
Section: Exposure Epidemiology and Regulatory Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bei konsekutiv (routinemäßig) epikutan getesteten spanischen Patienten (n = 3.678) rief Palladiumdichlorid 2 % pet. bei 8,6 % positive Reaktionen hervor, und nur 26 dieser 316 positiven Patienten waren nicht zugleich auch gegen Nickel sensibilisiert [46], was andernorts gemachte Beobachtungen bestätigt [47]. Epikutantestreaktionen auf Vanadium (getestet als Trichlorid 1 % pet.)…”
Section: Ergebnisseunclassified